2018
DOI: 10.1111/ppe.12526
|View full text |Cite
|
Sign up to set email alerts
|

Are selection criteria for healthy pregnancies responsible for the gap between fetal growth in the French national Elfe birth cohort and the Intergrowth‐21st fetal growth standards?

Abstract: Background The Intergrowth‐21st (IG) project proposed prescriptive fetal growth standards for global use based on ultrasound measurements from a multicounty study of low‐risk pregnancies selected using strict criteria. We examined whether the IG standards are appropriate for fetal growth monitoring in France and whether potential differences could be due to IG criteria for “healthy” pregnancies. Method We analysed data on femur length and abdominal circumference at the second and/or the third recommended ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
5
23
0
Order By: Relevance
“…which the proportions below the 10 th centile were far lower than 10% [17]. AC and FL discrepancies between French and INTERGROWTH-21 st centiles were also demonstrated using a very large sample of low-risk pregnancies belonging to the French Elfe cohort [35]. Similar results were published by Cheng et al, who showed large differences between the INTER-GROWTH-21 st standards and the Chinese biometry standards using data collected on more than 10,000 unselected pregnancies.…”
Section: Plos Onesupporting
confidence: 82%
“…which the proportions below the 10 th centile were far lower than 10% [17]. AC and FL discrepancies between French and INTERGROWTH-21 st centiles were also demonstrated using a very large sample of low-risk pregnancies belonging to the French Elfe cohort [35]. Similar results were published by Cheng et al, who showed large differences between the INTER-GROWTH-21 st standards and the Chinese biometry standards using data collected on more than 10,000 unselected pregnancies.…”
Section: Plos Onesupporting
confidence: 82%
“…Our study population prone to malaria was quite selected and this maybe introduce a bias. However, a recent study showed that the difference between the two charts remained while using fetal biometric measurements from pregnant women as healthy as those in the Intergrowth 21st study [43].…”
Section: Discussionmentioning
confidence: 99%
“…Women were treated and followed prospectively as part of the usual health care management in France before, during and after pregnancy. In France, once having a positive pregnancy test, the woman may be checked with the same gynecologist throughout her pregnancy, including 3 ultrasound scans (1 st at 12 weeks, 2 nd at 22–24 weeks, and 3 rd at 30–35 weeks of pregnancy, respectively) [16–19]. Specifically, from the EGB, we selected data on all the variables that characterized a pregnant woman (age, insurance, government financial support, geographic code) as well as the variables that described the physician visits (date in day/month/year, prescriber, diagnosis, procedure).…”
Section: Methodsmentioning
confidence: 99%